2020
DOI: 10.3390/jcm9040901
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disordered Breathing in Hypertrophic Cardiomyopathy—Current State and Future Directions

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiomyopathy and sleep disordered breathing (SDB) is a treatable risk factor that has been seen to occur concurrently, and is known to propagate mortality and morbidity in a number of cardiovascular disease states including heart failure, and indeed hypertrophic cardiomyopathy. In this review, we summarize past studies that explored the simultaneous occurrence of HCM and SDB, and the pathophysiology of SDB in relation to heart failure, arrhythmia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Obstructive sleep apnea (OSA) is a common sleep disturbance in adults that has been increasingly implicated in the pathogenesis and complications of cardiovascular disease, including HCM 2,3 . Studies have reported that OSA is common in patients with HCM with a prevalence of 32% to 71% 4 . OSA is independently associated with increased structural and functional cardiac impairment in patients with HCM, including higher NYHA functional classes, and a worse quality of life 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a common sleep disturbance in adults that has been increasingly implicated in the pathogenesis and complications of cardiovascular disease, including HCM 2,3 . Studies have reported that OSA is common in patients with HCM with a prevalence of 32% to 71% 4 . OSA is independently associated with increased structural and functional cardiac impairment in patients with HCM, including higher NYHA functional classes, and a worse quality of life 3 .…”
Section: Introductionmentioning
confidence: 99%